PENGARUH PENGUMUMAN DEVIDEN TERHADAP PERUBAHAN HARGA SAHAM SEBELUM DAN SESUDAH EX-DIVIDEND DATE DI BURSA EFEK JAKARTA (BEJ) - Nana Lestary Nasir; Raina Linda Sari (Ekonomi dan Keuangan, 2014)
This study aims to determine the difference in the stock price caused by the announcement of the dividend before and after the ex-dividend date on LQ45, this giving an overview to the investor in making an investment decision on LQ45 companies in the Jakarta Stock Exchange ( JSX ).Data used for this this study is secondary data that was obtained from companies which are included to LQ45 group and listed on the Jakarta Stock Exchange during the period of January 2008 to December 2012. In this study analysis used is Paired Sample T-Test ( two different test average ) by using SPSS 17.The study result can be concluded that stock prices in Indonesia increasingafter the ex-dividend date, can beseen from stock price change of each stock sample overall was found any significant differences changes in stock prices before and after the ex-dividend date is statistically caused by dividend announcement on each sample company, and from the results of the test sample stock portfolio that showing changedof the overall stock price LQ45 in 2008 to 2012 is statistically reflected in the value of the dividend distributed.Keywords : Dividend Announcement, Ex-Dividend Date, Stock Price